Tuber mixtecorum (Tuberaceae, Pezizales) a new truffle in the Maculatum clade from Mexico - García-Jiménez, Jesús; Ayala-Vásquez, Olivia; Guevara-Guerrero, Gonzalo; Garza-Ocañas, Fortunato; de La Fuente, Javier Isaac (Phytotaxa, 2021)
Tuber mixtecorum is described as a new species from Mexico based on morphological and molecular evidence. This species belongs to the Maculatum clade and is characterized by its subtomentose to glabrous, whitish to pale brown peridium, dark brown gleba, ellipsoid reticulate-alveolate ascospores (15–33.9 × 11.3–23.3 µm), and the putative mycorrhizal association with Quercus castanea in Quercus-Pinus dry mixed forests.